(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Urban kampung in Indonesia has the characteristics of a high population density living in a limited amount of land. Residents of an urban kampung require a space that can be used together to carry out communal activities. However, the limited amount of land in a kampung causes these activities to occupy whatever land is available which often has uncertain ownership status. A team from the Department of Architecture UI built ’Popsyandu’ shelter in Kampung Palsigunung, Depok, West Java, using the ’flexible architecture’ approach to respond to the needs and issues of the kampung. Using qualitative methods and data collection through observation and interview, this paper attempts to discuss the application of flexible architecture in the design of ’Popsyandu’. The result shows that the application of ’flexible architecture’ approach is difficult to be comprehended by the residents of the kampung, even though the designers tried to involve the residents during the design and construction process. Therefore, the authors conclude that in adopting a flexible architecture to respond to certain issues, the designer must consider the capabilities of the user instead of just following the theories stated beforehand. © 2020 Dalhar Susanto, Widyarko, Nisrina Dewi Salsabila